2021
DOI: 10.21203/rs.3.rs-266050/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial signatures in the lower airways of mechanically ventilated COVID19 patients associated with poor clinical outcome

Abstract: Mortality among patients with COVID-19 and respiratory failure is high and there are no known lower airway biomarkers that predict clinical outcome. We investigated whether bacterial respiratory infections and viral load were associated with poor clinical outcome and host immune tone. We obtained bacterial and fungal culture data from 589 critically ill subjects with COVID-19 requiring mechanical ventilation. On a subset of the subjects that underwent bronchoscopy, we also quantified SARS-CoV-2 viral load, ana… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 77 publications
2
5
0
Order By: Relevance
“…Our observation that integrated features of the upper respiratory tract microbiome and commensal viruses correlate with COVID-19 severity and outcome is complementary to a study of intubated COVID-19 patients which reported that mortality correlated with integrated features of lower respiratory tract microbiome, SARS-CoV-2 RNA levels, antibody levels, and transcriptome patterns ( 35 ). Thus, while the individual parameters investigated differed in these two studies, together they suggest that the entire airway, including both the upper and lower respiratory tract, is associated with COVID-19 outcomes.…”
Section: Discussionsupporting
confidence: 61%
“…Our observation that integrated features of the upper respiratory tract microbiome and commensal viruses correlate with COVID-19 severity and outcome is complementary to a study of intubated COVID-19 patients which reported that mortality correlated with integrated features of lower respiratory tract microbiome, SARS-CoV-2 RNA levels, antibody levels, and transcriptome patterns ( 35 ). Thus, while the individual parameters investigated differed in these two studies, together they suggest that the entire airway, including both the upper and lower respiratory tract, is associated with COVID-19 outcomes.…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, the ACE2 gene has been shown to be negatively regulated in some cells during SARS-CoV-1 infection [ 45 ]. These variations in the susceptibility of cells associated with the respiratory system have already been described in other studies that have demonstrated topographic differences in the replication of SARS-CoV-2 in the respiratory tract and almost undetectable levels of subgenomic viral material at the bronchoalveolar level [ 48 ].…”
Section: Resultssupporting
confidence: 62%
“…Analysis of patient samples in Nashville (n = 38 mild to moderate positive, 21 negative) revealed the complexity of interaction between viruses and bacteria in the upper respiratory tract, as differences in the airway microbiome were reported to be dependent on the SARS-CoV-2 viral load [16]. Similarly, in the lower airway, samples obtained through bronchial lavage (n = 142 positives) were enriched with oral bacteria in COVID-19 patients who had worse clinical outcomes, but mortality was better predicted by viral load and host immune response [17]. While microbial differences were present, SARS-CoV-2 and host factors were the most important in disease severity in both studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the NP microbiome in SARS-CoV-2 positive and negative samples have found a range of observations; from no differences in those with mild COVID-19 to species-specific alterations that differed in reports from different cities and patient populations [2][3][4]16,17]. In one study of co-infections in the respiratory tract (n = 100 positive) that found limited viral genetic variation among patients, the authors suggested that the presence of particular species (e.g., Clostridium botulinum, Bacillus cereus and Halomonas spp.)…”
Section: Introductionmentioning
confidence: 99%